A cyclometalated trinuclear Ir(iii)/Pt(ii) complex as a luminescent probe for histidine-rich proteins. Issue 6 (22nd January 2020) - Sarkar, Ankita; Kumar, Ravi; Das, Bishnu; Ray, Partho Sarothi; Gupta, Parna
Abstract : A trinuclear luminescent organometallic Pt–Ir–Pt complex acts as an efficient protein staining agent due to reversible binding to histidine-rich proteins. Abstract : Organometallic complexes have important application in the field of protein staining, with potential for use in proteomic analysis. The rational synthesis of a trinuclear luminescent organometallic complex with two platinum(ii ) centres appended to the cyclometalated ligand of the iridium(iii ) centre is reported here. Two di-2-picolylamine groups bonded to the cyclometalated phenyl pyridine moiety provide three coordinating sites to each platinum centre. The replacement of chloride in the fourth coordination site of two square planar platinum metal centres with the imidazole nitrogen or sulphur atom of histidine/cysteine is evident from the change in luminescence intensity upon binding these amino acids. The increase in luminescence emission intensity upon binding of histidine to the organometallic complex allowed it to be used as a protein staining agent. Reversibility of staining upon washing with imidazole enhances the possibility of its application in mass spectrometric analysis.